Bacteria-Derived Carbon Dots Inhibit Biofilm Formation of Escherichia coli without Affecting Cell Growth - Lin, Fengming; Li, Chengcheng; Chen, Zhan (Frontiers in Microbiology, 2018)
Biofilms are deleterious in many biomedical and industrial applications and prevention of their formation has been a pressing challenge. Here, carbon dots, CDs-LP that were easily synthesized from the biomass of Lactobacillus plantarum by one-step hydrothermal carbonization, were demonstrated to prevent biofilm formation of E. coli. CDs-LP did not thwart the growth of E. coli, indicating the anti-biofilm effect was not due to the bactericidal effect. Moreover, CDs-LP did not affect the growth of the animal cell AT II, showing low cytotoxicity, good safety and excellent biocompatibility. Therefore, CDs-LP could overcome the cytotoxicity issue found in many current antibiofilm agents. CDs-LP represent a new type of anti-biofilm materials, opening up a novel avenue to the development of biofilm treatment.